«The Journal of History fulfilled its purpose of imparting knowledge». Interview with Rodrigo Quesada Monge - Pacheco Calderón, Daniela; Núñez-Marín, Francisco Javier (Revista de historia., 2025)
The interview captures the memories of Costa Rican historian Rodrigo Quesada Monge (1952), who recalls the role of Dr. Germán Tjarks (1919-1997), one of the founders of the Revista de Historia de la Escuela de Historia (History Journal of the School of History). Through anecdotes and events, it takes a look at the founding process and the context in which it was organized, as well as mentioning other founders and reflecting on the role of the discipline of history from 1975 to the present. It also highlights the importance of disseminating history and how it fulfills its role of promoting Latin American historiography in the academic sphere. The interview also includes contributions from Maritza Chaves, Quesada Monge’s wife. This project is part of the commemoration of the 50th anniversary of the Revista de Historia de la Universidad Nacional.